The Influence of Work Environment and Organizational Culture on Employee Work Commitment with Employee Work Motivation as an Intervening Variable Tiara Hospital Bekasi - Suzanti, Nurmalia; Saluy, Ahmad Badawi (Dinasti Publisher, 2023)
This research aims to describe the influence of the work environment and organizational culture on employee work commitment with motivation as an intervening variable at Tiara Bekasi Hospital. This research was conducted at Tiara Bekasi Hospital using a sample size of 226 respondents. The sampling technique is non-probability sampling or saturated sampling. The data analysis technique used is SEM-PLS, the calculations of which are assisted by the SmartPLS 3.0 program. Partial Least Square (PLS) model evaluation analysis was carried out by evaluating the outer model and evaluating the inner model. The results of data analysis show that the work environment and organizational culture have a positive and significant effect on commitment. Then motivation has a positive and significant effect on commitment. Meanwhile, the work environment has a positive and significant effect on motivation. Then motivation has a positive and significant effect on employee commitment. The results of data analysis also show that motivation can mediate positively and significantly between the influence of the work environment on commitment. Meanwhile, motivation can mediate positively and significantly between organizational culture and employee work commitment.